The Teacher Education and Training Policy for the Development of Teacher Identity - Tütüniş, Birsen (My University, 2019)
English teacher education programs as a source of knowledge and skills aim to prepare students for their future profession but not in professionalism. While student teachers are navigating their way towards professionalism, they need to shift identities from student to novice teacher, which is not an easy process, and they need support. Shanahan, Meehan, and Moggie (1994) define professionalism as “the process of using education and certification to enhance the quality of performance of those within an occupational field." Foreign language teacher education needs to lessen the discrepancy between personal knowledge and social reality, the teacher agencies outside. TEFL programs in Turkey and elsewhere equip student teachers with theoretical knowledge that is not helpful in the quest of teacher identity. This presentation will discuss the pros and cons of TEFL programs with examples of student teacher performances.